Lesbian camp: An unearthing - Nielsen, Elly-Jean (Journal of Lesbian Studies, 2016)
Camp—a sensibility, a style, and a form of artistic selfexpression—is an elusive concept said to be in the eye of the beholder. To refute Susan Sontag’s (1966) claims that camp is apolitical and not especially homosexual, a number of recent scholarly works have been geared toward revealing camp’s fundamental gayness. With the odd footnote aside, lesbian camp has been collapsed into the category of gay male camp, if not eclipsed entirely. Despite the negligible efforts made to legitimize lesbian camp, there are numerous salient cultural examples one might draw on to illustrate, typify, and substantiate a lesbian camp sensibility. I lay the ground work for this scholarly exercise by outlining various definitions and critiques of camp, and by discussing its history and application to queer theory. Then, to unveil lesbian camp, three nonmutually exclusive categories are discussed: classic, erotic, and radical. By gathering various strands of inquiry, and various textual examples (e.g., photography, artistic performances, and literary tropes), this article attempts to reach a more inclusive and nuanced understanding of lesbian camp.
Keywords: approches et analyses; butch/femme; discipline; personnes lesbiennes; psychologie; queer; ressource en ligne; sciences humaines